The hospitality of refugees at the memorial of Shoah in Milan. The educational function of memory - Pasta, Stefano (Rivista di Storia dell’Educazione, 2017)
In 2015 and 2016 the Shoah Memorial Foundation and the Community of Sant’Egidio welcomed – in the Memorial itself, in an area below “Binario 21” (Platform 21) in Milan Central Statio – some thousands of refugees, who had stopped momentarily in Milan, to continue then their journey towards Northern Europe. For many citizens of Milan – among whom a lot of young people – the Memorial and the meeting with the refugees have had an educational function, and this has stricken and affected those involved in Holocaust Education. The action of the Memorial is striking also because it is set in a more general silence of the migration museums and of the memorial sites towards the flux of refugees coming to Europe.